Development and validation of deep learning-based automatic brain segmentation for East Asians: A comparison with Freesurfer - Moon, Chung-Man; Lee, Yun Young; Hyeong, Ki-Eun; Yoon, Woong; Baek, Byung Hyun; Heo, Suk-Hee; Shin, Sang-Soo; Kim, Seul Kee (Frontiers in Neuroscience, 2023)
Purpose: To develop and validate deep learning-based automatic brain segmentation for East Asians with comparison to data for healthy controls from Freesurfer based on a ground truth. Methods: A total of 30 healthy participants were enrolled and underwent T1-weighted magnetic resonance imaging (MRI) using a 3-tesla MRI system. Our Neuro I software was developed based on a three-dimensional convolutional neural networks-based, deep-learning algorithm, which was trained using data for 776 healthy Koreans with normal cognition. Dice coefficient (D) was calculated for each brain segment and compared with control data by paired t-test. The inter-method reliability was assessed by intraclass correlation coefficient (ICC) and effect size. Pearson correlation analysis was applied to assess the relationship between D values for each method and participant ages. Results: The D values obtained from Freesurfer(ver6.0) were significantly lower than those from Neuro I. The histogram of the Freesurfer results showed remarkable differences in the distribution of D values from Neuro I. Overall, D values obtained by Freesurfer and Neuro I showed positive correlations, but the slopes and intercepts were significantly different. It was showed the largest effect sizes ranged 1.07–3.22, and ICC also showed significantly poor to moderate correlations between the two methods (0.498≤ICC≤0.688). For Neuro I, D values resulted in reduced residuals when fitting data to a line of best fit, and indicated consistent values corresponding to each age, even in young and older adults. Conclusion: Freesurfer and Neuro I were not equivalent when compared to a ground truth, where Neuro I exhibited higher performance. We suggest that Neuro I is a useful alternative for the assessment of the brain volume.